The role of religiosity types in the phenomenology of hallucinations: A large cross-sectional community-based study in a predominantly Muslim society - Salma M. Khaled (13847737) (2022)
Religiosity is a multidimensional construct known to influence the occurrence of hallucinations. However, it remains unknown how different religiosity types affect clinically relevant phenomenological features of hallucinations. Therefore, we wished to explore associations between intrinsic and extrinsic (non-organizational and organizational) religiosity and hallucinations severity, distress or impact on daily function in a non-clinical Muslim population. We recruited a representative sample of full-time students at Qatar's only national university via systematic random sampling and administered the Questionnaire of Psychotic Experiences online. The study design was cross-sectional. Using structural equation modeling, we estimated effects of the religiosity types on hallucinations severity, distress or impact on daily function in the past week while accounting for sociodemographic variables, anxiety, depressive symptoms, and, delusions. Extrinsic non-organizational religiosity (ENORG) was associated with experiencing reduced distress or impact on daily function from hallucinations both directly and indirectly through intrinsic religiosity. In contrast, extrinsic non-organizational religiosity (EORG) was associated with increased hallucinations distress or impact albeit only through higher intrinsic religiosity. We found no association between any religiosity types and hallucinations severity. Younger and married participants from lower socio-economic class had comparatively more severe hallucinations and more distress from them. Qatari nationality was positively associated EORG and negatively associated with hallucinations distress or impact. Evidence of differential associations between the religiosity types, socioeconomic and cultural groups, and distress or impact from past week's hallucinations supports the importance of alignment between religious, mental health, and well-being education. Other Information Published in: Schizophrenia Research License: https://www.elsevier.com/tdm/userlicense/1.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.schres.2022.11.003